Remote evaluations for humanitarian parole of asylum seekers to the United States - The case of MA: English - Febles Simeon , Olivia; Cuneo, C. Nicholas (Torture Journal, 2023)
This case seeks to demonstrate the value of remote evaluations conducted by health professionals for the purpose of applying for humanitarian parole. In this case, a survivor of labor trafficking, kidnapping, and sexual violence in her home country endures additional physical and psychological suffering after experiencing physical and sexual assaults while awaiting entry into the United States to seek asylum. As increasing numbers of migrants seeking protection arrive at the United States’ southern border, immigration enforcement deterrence policies keep many asylum seekers in limbo. Remote evaluations conducted by health professionals to document physical and psychological disorders for the purpose of applying for humanitarian parole can help to prioritize the most vulnerable cases (Mishori et al, 2021).